Designing Information Systems for Payroll Process for National University-Based University Lecturers: Designing Information Systems for Payroll Process for National University-Based University Lecturers - Nizar Nizar; Septi Andriyana; Aris Gunaryati (Jurnal Mantik, 2020)
Payroll is one of the important things in an organization. Salary is one of the factors that inspire employees. Therefore a timely payroll process will make employees more motivated to achieve organizational goals. The purpose of this research is to build a simple information system to process employee payroll with a case study at the National University. This information system was built using the programming languages PHP, CSS and Javascript as a user interface, and MySQL as a database. The method used in this study is the waterfall method. The stages of the method used are analysis, design, coding and testing